Image Processing for Pathological Visualization in Multitemporal Convoluted TIRI - Khan, Masood Mehmood; Arthur, Daniel; Barclay, Luke (IEEE-EMBS, 2012)
The convoluted nature of thermal infrared radiation and poor understanding of the physical mechanismsof human emittance, make objective image acquisition and processing protocols prerequisite for meaningful diagnostic specificity. A longitudinal dataset of clinical thermal infrared images was objectively processed to facilitate visualization of osseous stress pathology in the lower limbs.. This paper details processing of 500+ thermal infrared images acquired during a recent three month clinical study into osseous stress pathology in the lower limbs of Australian Army basic trainees. The use ofthermal chroma-keying in segmentation and multitemporal image calibration is demonstrated. The ‘OpenSURF’ implementation of the scale and rotation-invariant interest point detector and escriptor are shown to be performant in registration of multitemporal clinical thermal infrared image data. Thermal ‘signs’ observed in longitudinal images appear to be revealing detectable changes in osseous stress pathophysiology.